Catalan food : culture & flavors from the Mediterranean - Olivella, Daniel; Wright, Caroline (Clarkson Potter/Publishers, 2018)
In proud, vibrant Catalonia, food is what brings people together<U+2014>whether neighbors, family, or visitors. By the sea, over a glass of chilled vermouth and the din of happily shared, homemade Pica Pica (tapas) is where you<U+2019>ll find the most authentic Catalonia. The region is known for its wildly diverse indigenous ingredients, from seafood to jamon Ibérico to strains of rice, and richly flavored cuisine that has remained uniquely Catalan throughout its complex and fraught history. In Catalan Food, the recipes are intended to be cooked leisurely and with love<U+2014>the Catalan way. Featuring traditional dishes like Paella Barcelonata (Seafood Paella) and Llom de Porc Canari (Slow-roasted Pork Loin), as well as inventive takes on classics like Tiradito amb Escalivada (Spanish Sashimi with Roasted Vegetable Purees) and Amanida de Tomàquet amb Formatge de Cabra (Texas Peach and Tomato Salad with Goat Cheese), Catalan Food brings heritage into any home cook<U+2019>s kitchen, where Catalonia<U+2019>s cuisine was born. To know a culture, you must taste it; none is more rich and stunningly delicious than Catalonia<U+2019>s.